Role of Breast Ultrasonography in Adding Diagnostic Value in Case of Dense Breasts Detected by Mammography - Panta, Sujata; Shahi, Rajive Raj; Panta, Sujit; Basnet, Bina; Rai, Kalpana; Tulachan, Neeraj Basanta (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: Mammography is a simple and effective tool in early detection of breast lesions. However its sensitivity is less in dense breast. The aim of the study is to see whether addition of ultrasonography adds on to the diagnostic value by finding more breast lesions in evaluation of mammographic dense breasts or not. Methods: The hospital data of all the patients who underwent mammography in the Department of Radiology of Shree Birendra Hospital, Kathmandu over a period of two and a half years from November 2017 to April 2020 were retrieved and retrospectively analyzed. The mammographic findings of patients with dense breast were compared with the corroborative ultrasonographic findings. Discrepancy in positive findings between the two imaging modalities was studied.   Results: Out of 536 patients studied, 238 patients had mammographic dense breast. Comparative study showed 82 cases with positive findings on mammography alone, compared to 114 cases with positive findings on combined mammography and ultrasonography with p-value < 0.05 which is statistically significant.Conclusions: Ultrasonography is a useful additional imaging modality in evaluation of mammographic dense breast by finding more breast lesions compared to Mammography alone.